Energy efficient routing for telecommunication networks with multiperiod traffic - Santos, Dorabella (2013)
The exponential growth of tra c demand, and supporting network infrastructures, is leading to serious energy consumption issues. With proper routing, some network links can be put on a sleep mode if demands can be routed through other links and, with multiperiod tra c, the sleeping links can change between periods. In this paper, we address the energy e cient routing problem, and we study the tradeo between energy savings and percentage of routing paths allowed to change between periods. We present an ILP model de ning the energy e cient routing problem and we propose a GRASP based heuristic to compute good routing solutions.